Role of Gamma-Glutamyl Transferase, High Sensitivity C Reactive Protein and Apolipoprotein B as A Marker of Disease Severity in Psoriasis - Shofiyah, Laily; Ardyanto, Tonang Dwi; Prabowo, Nurhasan Agung; Aprilningsih, Hendrastutik; Myrtha, Risalina; Kuncorowati, Niken Dyah Aryani; Suwandono, Adji; Nugroho, Novianto Adi; Sari, Maria Galuh Kamenyangan; Dyanneza, Frieska (Poltekkes Kemenkes Surabaya, 2025)
Psoriasis can develop into systemic psoriasis, which primarily affects the liver, bile ducts, and cardiovascular system. Assessing the severity of psoriasis was crucial for determining treatment and cardiovascular disease risk. The aim of this study was to determine the role of Gamma-Glutamyl Transferase (GGT), High Sensitivity C-Reactive Protein (HS-CRP), and apolipoprotein B (APO B) in assessing the severity of psoriasis. Methods: This study was a cross-sectional, observational analytic study. A total of 33 psoriasis patients were tested for GGT, HS-CRP, APO B levels, and the Psoriasis Area and Severity Index (PASI) score. Results: The average GGT level was 70.75±56.47 u/L, the average HS-CRP level was 0.91±1.03 mg/L, the average APO B level was 110.09±26.47 mg/dL, and the average PASI score was 11.70±4.54. 12.1% of patients had mild psoriasis, 51.5% had moderate psoriasis, and 36.4% had severe psoriasis. There was a positive and strong correlation between GGT and PASI score, HS-CRP and PASI score, and APO B and PASI score. The multivariate correlation between GGT, HS-CRP, and APO B with PASI score had a value of R = 0.874, F = 31.145, p = <0.001. Conclusion: The multivariate correlation between GGT, HS-CRP, and APO B with PASI scores shows a positive and strong correlation, thus it useful for assessing the severity of psoriasis and evaluating the likelihood of cardiovascular disease.